AUDIT MARKET CONCENTRATION – EVIDENCE FROM CROATIA - Sanja Sever Mališ; Mateja Brozović (Ekonomski Vjesnik, 2015)
Statutory audit is designated to protect the public interest and has a significant impact on the overall economy. There are concerns that the Big Four audit firms have become too dominant and that the collapse of one of these firms would disrupt the whole financial system. In terms of revenues received, the total market share of the Big Four audit firms for listed companies exceeds 90% in a vast majority of European Union Member States. Prior studies have shown that high audit market concentration limits the choice of auditor for large companies and sets a high barrier of entry for mid-tier audit firms, while the effect on audit quality and audit fees is still unclear. Therefore, the regulators are considering reforms to dilute the Big Four’s dominance and improve competition in the audit market. The paper reviews the proposed and implemented measures that are the most common, together with their advantages and drawbacks. In addition, the characteristics of the audit market in Croatia are investigated, with a focus on market concentration measured by standard measures such as the Concentration rate, the Herfindahl Hirschman Index and the Gini coefficient. According to market shares based on total clients’ assets and revenues, the audit market for listed companies is moderately to highly concentrated, with a decrease in the five-year period (2013 compared to 2008).